“I am not the same as before”: a mixed-methods study on depression in people with spinal injury in Qatar - Al Shamari, Badriya Khalifa; O’Hara, Lily (Frontiers in Psychiatry, 2024)
incidence of spinal injury is high in the Middle East and North African region (MENA) due to the high incidence of road traffic crashes. A spinal injury may trigger mental health issues. Compared to the general population, people with spinal injury are at higher risk for developing major depression, anxiety, post-traumatic stress disorders, substance abuse, and suicide.Objectives: The objectives of the study were to determine depression prevalence; identify relationships between depression and cause and site of spinal injury, sociodemographic factors, and social support; and explore the lived experiences of depression in people with spinal injury in Qatar.Methods: A sequential cross-sectional mixed methods study was conducted. In the quantitative component, the universal sample consisted of 106 consenting individuals presenting with spinal injury at Hamad General Hospital, Doha, Qatar between January and December 2020. The Patient Health Questionnaire-9 was used to assess levels of depression and the Medical Outcomes Study Social Support Survey was used to assess perceived social support. The cause and site of injury were obtained from patient records. In the qualitative component, semi-structured in-depth interviews were conducted with 12 purposively selected participants from the quantitative component.Results: In total, 69% of participants had some level of depression: 28% mild, 25.5% minimal, and 15% moderate to severe. Depression was not associated with socio-demographic factors, or the cause or site of spinal injury. Higher levels of emotional/informational support and positive social interaction were associated with milder depression. Spinal injury had a negative impact on participants' physical, mental, social, and spiritual wellbeing. Social support and religious faith were critical in assisting participants to cope with their new situation.Conclusions: Depression is prevalent among people with spinal injury attending health services. Early detection, referral, and treatment of depression are recommended. Strategies to enhance emotional/ informational support and positive social interaction should be developed and tested with people with spinal injury.Introduction: Spinal injury is a traumatic event impacting health, wellbeing, and quality of life. The